The mechanism of Chinese herbal formula HQT in the treatment of rheumatoid arthritis is related to its regulation of lncRNA uc.477 and miR-19b. Issue 2 (21st July 2020) - Wang, Maojie; Mei, Liyan; Liu, Zehao; Tang, Xuan; Wu, Xiaodong; Chen, Xiumin; Zhao, Yue; Huang, Qingchun; Huang, Runyue
Abstract: Rheumatoid arthritis (RA) pathogenesis has been associated with dysregulation of long noncoding RNA (lncRNA) and microRNA (miRNA) expression in serum and in lesioned tissue. In this study, a microarray assay was performed to study the profile of lncRNAs in the serum of RA patients and healthy donors, and a set of novel lncRNAs associated with RA was identified. For the remainder of the study, focus is on the top hit, lncRNA uc.477. The upregulation of lncRNA uc.477 and downregulation of miR‐19b were validated in the serum of RA patients compared to that of healthy donors, and similar results were further confirmed by quantitative real‐time PCR analysis of a cell line: RA‐derived human fibroblast‐like synoviocytes (HFLS‐RA). LncRNA uc.477 could interfere with the processing of pri‐miR‐19b to produce its mature form and thereby played a pro‐inflammatory role. In addition, Huayu Qiangshen Tongbi formula (HQT), a traditional Chinese medicine (TCM), has been shown to exert a promising therapeutic effect on RA and to exhibit long‐term safety in our previous clinical retrospective study. Importantly, HQT treatment normalized the levels of lncRNA uc.477 and miR‐19b in HFLS‐RA in vitro and in mouse models of collagen‐induced arthritis. HQT treatment, knockdown of lncRNA uc.477, and overexpression of miR‐19b resulted in a comparable inhibition of pro‐inflammatory cytokine gene expression in HFLS‐RA cells. Together, these data suggest that the therapeutic effects of HQT on RA are closely related to its modulation of lncRNA uc.477 and miR‐19b. Graphical Abstract: The therapeutic effect of Huayu Qiangshen Tongbi formula on rheumatoid arthritis is closely related to its modulation of lncRNA uc.477 and miR‐19b.